Analysis of clinical characteristics and health resource costs in children hospitalised for injuries in southern Sichuan, China - Lu, ZiWei; Wang, YinSu; Nie, Min; Li, JiaQin; Yu, YanHong; Zhuang, Yuan; Mao, Xiaoyan; Shen, Xing (Frontiers in Pediatrics, 2023)
Aim: To investigate the clinical characteristics and health resource costs among children hospitalised for injuries in Sichuan, China and to provide guidance for the prevention and treatment. Methods: We retrospectively analysed clinical data concerning children aged from 29 days to 18 years hospitalised for injuries from January 1, 2017, to December 31, 2021. Results: Among 5826 hospitalised children with injuries, males (63.6%), those in rural areas (40.3%), and adolescents (33.5%) were most commonly injured. Most injuries occurred at home (52.6%), and during summer. The most common injury types were falls, burns, road traffic injuries, poisoning, and foreign body injuries (32.0%, 17.9%, 13.6%, 8.8%, and 7.9%, respectively). After 2019, the proportion of intentional injuries among adolescent girls was significantly higher. Road traffic injuries were most commonly led to poor clinical outcomes (95%CI: 5.39-31.51), followed by falls (95%CI: 2.20-10.67). Adolescents were at higher risk of poor prognosis. Injuries occurring in rural areas, adolescents, road traffic injuries, and falls cost high health resource. Conclusion: Unintentional injuries among children remain serious. Therefore, targeted prevention and control measures for road traffic injuries and falls should be strengthened. Attention should be paid to intentional injuries among adolescent females.